Kontribusi Faktor Lingkungan Sekolah, Lingkungan Keluarga, dan Motivasi Berprestasi terhadap Nilai Modern Siswa Sekolah Lanjutan Tingkat Pertama (SLTP) di Kabupaten Gianyar, Bali - Dewa Made Alit (Graduate School, Universitas Negeri Yogyakarta, 2003)
This research was aimed at finding out: (1) modern values of SLTP students at Gianyar Regency; (2) the contribution of the school environment and the family environment both individual or in group toward student's achievement motivation; (3) the contribution of the achievement motivation toward student's modern values and (4) the direct contribution of the school environment and family environment toward students' modern values. The population of this research consists of all SLTP students in Gianyar Regency. The sample consists of 192 students established by using the proportional random sampling technique. The instrument was a questionnaire using to Likert's Scales. This study uses descriptive, regression and path analyses. The test of correlation and regression coefficient significance is (X— .05 level of significance.The descriptive analysis shows that students' school environment, family environment, achievement motivation and modern values, all are in the mediocre category. The value of regression analysis shows that the contribution of the school environment has coefficient correlation of 0.380 and the value of family environment has coefficient correlation of 0.308 each for the achievement motivation, and the contribution of achievement motivation toward students' modern values has coefficient correlation of 0.487. The result of the multiple regression analysis shows that there is positive and significant contribution of the school and family environment altogether, which has coefficient regression of 0.421 toward achievement motivation. Both variables can explain the students' achievement motivation variance, which is 17.7 %. The result of the path analysis shows that: (1) through achievement motivation there is indirect contribution of school environment, which has coefficient path regression of 0.098 and family environment which has coefficient path regression of 0.062 toward students' modern values, and (2) there is direct contribution of school environment which has coefficient path regression of 0.182 and family environment which has coefficient path regression of 0.329 toward students' modern values. Based on the research findings it can be concluded that there is direct contribution of school environment, family environment, and achievement motivation toward students' modern values. There is also indirect contribution to students' modern values through achievement motivation. Kata kunci: faktor lingkungan sekolah, lingkungan keluarga, motivasi berprestasi, nilai modern siswa